Sosioalisasi Pelayanan Prima Kepada Laundry Cahaya Terang - Nirmalawati, Nirmalawati; Monique Ds, Eska Prima; Febriansa, M Rahman; Yudi, Yudi; Nasution, Suswati (Universitas Dehasen Bengkulu, 2024)
This study explores the implementation of strategies for providing excellent customer service at